Albuminuria Screening with Urine Strip in Klong Luang Community, Pathum Thani, Thailand - Pipatsatitpong, Duangnate; Sangprasert, Pantip; Yuenyongchaiwat, Kornanong; Aunpad, Ratchaneewan (Science & Technology Asia, 2017)
This study was to determine albuminuria prevalence and risk associations of albuminuria in people who lived in Klong Luang community. This cross-sectional study was conducted in Klong Luang community, Pathum Thani province, Thailand. The mid-stream urine and blood samples were collected from all participants for albuminuria testing with urine strip and blood urea nitrogen and creatinine analysis, respectively. Binary logistic regression was used for risk association analysis. Among 239 participants enrolled, 32 (13.4%) subjects had albuminuria. Creatinine was a significantly independent risk association for albuminuria (p<0.045, α=0.05). Participants who lived in this community were 13.4% albuminuria prevalence and creatinine was an independent risk association for albuminuria. Thus, Primary Health Care Services should follow up subjects with albuminuria and provide health education program to the Klong Luang community.